1986
DOI: 10.1016/0002-8703(86)90461-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of myocardial infarct size by neutrophil depletion: Effect of duration of occlusion

Abstract: Experiments were performed in the dog to examine the effects of neutropenia on ultimate infarct size resulting from short (90 minutes) or prolonged (4 hours) circumflex coronary artery occlusion. Sheep antiserum to canine neutrophils was used to produce neutropenia. Control animals received nonimmune serum. Neutrophil infiltration into myocardial infarcts was examined using histopathologic techniques and a semiquantitative scoring system. In 90-minute occlusions with 24-hour reperfusion, neutropenia was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(97 citation statements)
references
References 25 publications
2
94
0
1
Order By: Relevance
“…Some researchers have hypothesized that neutrophils exacerbate muscle injuries by releasing reactive oxygen intermediates, including peroxides, hypochlorite, and superoxide. [47][48][49][50][51] During muscle healing, different populations of macrophages perform different roles, including phagocytosis and the release of growth factors. 52,53 CD-11b (also called Mac-1) is a neutrophil surface antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have hypothesized that neutrophils exacerbate muscle injuries by releasing reactive oxygen intermediates, including peroxides, hypochlorite, and superoxide. [47][48][49][50][51] During muscle healing, different populations of macrophages perform different roles, including phagocytosis and the release of growth factors. 52,53 CD-11b (also called Mac-1) is a neutrophil surface antigen.…”
Section: Discussionmentioning
confidence: 99%
“…18 By contrast, in dogs with neutrophil depletion, myocardial necrosis was reduced with ischemia of either 90 or 240 minutes. 5 Sharar et al 3 found, using a rabbit ear preparation and 6 hours of occlusion, that administration of anti-CD18 therapy immediately on reperfusion was as effective as that initiated 1 hour but not 4 hours later. No effect was observed when the antibody was administered after 12 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PMNs were shown to infiltrate eroded or ruptured plaques obtained from patients with acute coronary syndromes [119,120], and to participate in the pathogenesis of lethal myocardial reperfusion [121]. Notably, depleting PMNs resulted in reduced myocardial infarct size and a protected myocardium [122,123].…”
Section: Polymorphonuclear Leukocytesmentioning
confidence: 99%